2010
DOI: 10.1002/bit.22958
|View full text |Cite
|
Sign up to set email alerts
|

Proteins conjugated to poly(butyl cyanoacrylate) nanoparticles as potential neuroprotective agents

Abstract: Poly(butyl cyanoacrylate) (PBCA) nanoparticles (NPs) can penetrate blood-brain barrier providing the means for drug delivery to the central nervous system. Here, we study attachment of superoxide dismutase (SOD) and anti-glutamate N-methyl D-aspartate receptor 1 (NR1) antibody to PBCA NPs with the ultimate goal to design neuroprotective therapeutics for treatment of secondary spinal cord injury. Synthesis of monodispersed, ∼200 nm-diameter PBCA NPs was performed using polymerization at pH 2.0 with Dextran 70,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…with a Teflon-coated stirring bar. 31 After overnight polymerization, the reaction was stopped by adding 1 mL of 0.1 mol/L NaOH, and the nanoparticle suspension was filtered twice through filter paper (VWR Grade 410 with 1 mm particle retention) in Buchner funnel via suction filtration to remove crystallized n-Butylcyanoacrylate. Excess of surfactant was removed by repeated centrifugation (4,500 r.c.f., 1.5 hours; Allegra 64 R centrifuge, Beckman Coulter, Brea, CA, USA).…”
Section: Preparation Of Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…with a Teflon-coated stirring bar. 31 After overnight polymerization, the reaction was stopped by adding 1 mL of 0.1 mol/L NaOH, and the nanoparticle suspension was filtered twice through filter paper (VWR Grade 410 with 1 mm particle retention) in Buchner funnel via suction filtration to remove crystallized n-Butylcyanoacrylate. Excess of surfactant was removed by repeated centrifugation (4,500 r.c.f., 1.5 hours; Allegra 64 R centrifuge, Beckman Coulter, Brea, CA, USA).…”
Section: Preparation Of Particlesmentioning
confidence: 99%
“…To study effect of targeting, we also decorated the surface of these bulk-loaded SOD-PLGA NPs by anti-NR1 antibody using the same crosslinking chemistry as in our in vitro study. 31 The goal of this study was to determine whether enhanced delivery of targeted antioxidant NPs to the site of neuronal injury can reduce the degree of secondary damage.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody attachment to NP was confirmed by incubating the NP preparations with a fluorescent secondary antibody (AF488) recognizing the anti-AQP4 antibody. 27,57 Fluorescence intensity of NP linked to anti-AQP4 antibody was substantially higher than that of control NP preparations (Figure 1c). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 (mass of resveratrol/mass of dried NP).…”
Section: Synthesis and Characterization Of Multifunctional Polymeric mentioning
confidence: 91%
“…Similarly, Lin and colleagues reported that polysorbate 80-coated PBCA nanoparticles loaded with HRP or enhanced green fluorescent protein (EGFP) can deliver these proteins to the brain in a rat model of TBI [427]. Another study evaluated dextran and polysorbate 80-coated PBCA nanoparticles carrying covalently immobilized SOD1 and anti-glutamate N-methyl D-aspartate receptor 1 antibody [428]. These protein-PBCA conjugates were shown to prevent neuronal cell death mediated by superoxide radicals O 2 ·– toxicity in the rat cerebellar cells.…”
Section: Particle-based Carriers For Cns Delivery Of Proteinsmentioning
confidence: 99%